2020
DOI: 10.1101/2020.07.30.228130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of nonlinguistic statistical learning: From neural entrainment to the emergence of explicit knowledge

Abstract: Humans are highly attuned to patterns in the environment. This ability to detect environmental patterns, referred to as statistical learning, plays a key role in many diverse aspects of cognition. However, the spatiotemporal neural mechanisms underlying implicit statistical learning, and how these mechanisms may relate or give rise to explicit learning, remain poorly understood. In the present study, we investigated these different aspects of statistical learning by using an auditory nonlinguistic statistical … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
2
5
0
Order By: Relevance
“…Interestingly, the ITPC differences between conditions (temporally-local vs. global) emerged during the experiment in chunk-rate peaks, but not in telement-rate peaks, suggesting that rapid learning could modulate neural entrainment to auditory sequences with different regularities at the chunk-rate level. Similarly, a previous study (Moser et al, 2021) found significant differences in non-linguistic triplet-rate ITPC peaks between structured and random conditions, occurring during early exposure. This ITPC difference suggests a fine shift in sequence encoding, with different regularities from single elements to integrated chunks.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, the ITPC differences between conditions (temporally-local vs. global) emerged during the experiment in chunk-rate peaks, but not in telement-rate peaks, suggesting that rapid learning could modulate neural entrainment to auditory sequences with different regularities at the chunk-rate level. Similarly, a previous study (Moser et al, 2021) found significant differences in non-linguistic triplet-rate ITPC peaks between structured and random conditions, occurring during early exposure. This ITPC difference suggests a fine shift in sequence encoding, with different regularities from single elements to integrated chunks.…”
Section: Discussionsupporting
confidence: 69%
“…The processing of different auditory features is thought to be lateralized (e.g., Tervaniemi & Hugdahl, 2003): left for temporal features and right for spectral features (Zatorre & Belin, 2001), which seems to be the case also for newborns (DeCasper & Prescott, 2009). Entrainment to a structured sequence in a statistical learning task showed similar lateralization of brain activity to the current one compared to a non-structured sequence in adults with better performance (Moser et al, 2021). This brings up the possibility of an interaction between entrainment and statistical learning, as we have proposed above.…”
Section: Discussionmentioning
confidence: 92%
“…One possibility is that in the present study the concurrent speech motor task specifically disrupted early-level auditory-motor processing of speech sounds, which impaired participants' ability to learn statistical regularities in speech streams. During processing of structured auditory streams, neural oscillations are entrained to their repeating statistical structures as well as their elements, either syllables or tones (Batterink et al, 2015b(Batterink et al, , 2019Batterink & Paller, 2017;Bogaerts et al, 2020;Doelling & Assaneo, 2021;Moser et al, 2021). The prevalent hypothesis is that neural oscillations reflect phases of high and low excitability of the neurons involved (Giraud & Poeppel, 2012;Lakatos et al, 2005;Ten Oever & Martin, 2021).…”
Section: Further Speculation and Interpretation Of The Main Findingsmentioning
confidence: 99%
“…Does the speech motor system play a domain-general role in auditory SL or does the speech motor system play a specific role in acquiring patterns and regularities from sequences of speech sounds specifically? Intriguingly, SL of patterns in tone sequences has also been shown to engage frontal motor regions in the left hemisphere (Moser et al, 2021;Farthouat et al, 2017). This has led to a proposal that the left-lateralized motor system could contribute to auditory SL in a domaingeneral manner.…”
mentioning
confidence: 99%